Dysphagia and Mortality Risk in Individuals With Primary Progressive Apraxia of Speech - Gabriela Meade; Nha Trang Thu Pham; Sarah M. Boland; Heather M. Clark; Joseph R. Duffy; Jennifer L. Whitwell; Hugo Botha; Keith A. Josephs; Rene L. Utianski (Annals of Clinical and Translational Neurology)
ABSTRACT Individuals with primary progressive apraxia of speech (PPAOS) often develop parkinsonism and dysphagia. To evaluate the clinical correlates and impact of dysphagia in this population, we compared enrollment visit data between individuals with (n = 12) versus individuals without (n = 44) dysphagia symptoms. The group with dysphagia had more motor speech symptoms and parkinsonism. Longitudinal analysis revealed that almost everyone developed dysphagia before dying; the average time to death after developing dysphagia was 5.43 years and complications of dysphagia resulted in mortality for 35% of the individuals for whom data were available. These results emphasize the need for dysphagia management and provide useful prognostic estimates.